2020
DOI: 10.1186/s12885-020-07513-w
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian cancer cells direct monocyte differentiation through a non-canonical pathway

Abstract: Background Alternatively-activated macrophages (AAMs), an anti-inflammatory macrophage subpopulation, have been implicated in the progression of high grade serous ovarian carcinoma (HGSOC). Increased levels of AAMs are correlated with poor HGSOC survival rates, and AAMs increase the attachment and spread of HGSOC cells in vitro. However, the mechanism by which monocytes in the HGSOC tumor microenvironment are differentiated and polarized to AAMs remains unknown. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…We suspect that early changes in tumor development may differentiate monocytes in a tissue-specific manner. Others have shown that the co-culture of PBMC-derived monocytes with ovarian cancer cell lines was sufficient for alternative macrophage development through TGF-alpha (Fogg et al 2020). We hypothesize that the macrophage-to-monocyte ratio could be an indicator of HGSC progression.…”
Section: Discussionmentioning
confidence: 78%
“…We suspect that early changes in tumor development may differentiate monocytes in a tissue-specific manner. Others have shown that the co-culture of PBMC-derived monocytes with ovarian cancer cell lines was sufficient for alternative macrophage development through TGF-alpha (Fogg et al 2020). We hypothesize that the macrophage-to-monocyte ratio could be an indicator of HGSC progression.…”
Section: Discussionmentioning
confidence: 78%
“…Others have shown that the co-culture of peripheral blood mononuclear cells (PBMC) derived monocytes with ovarian cancer cell lines was sufficient for alternative macrophage development through TGF-alpha. 55 We hypothesize that the macrophage-to-monocyte ratio could be an indicator of HGSC progression. This concept was recently applied within a melanoma and renal cell carcinoma context, 34 showing that the macrophage-to-monocyte ratio positively correlated with tumor Treg infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, several mechanisms have been elucidated that tumor-derived factors trigger monocyte differentiation into M2-like macrophages. In high-grade serous ovarian carcinoma (HGSOC), a high level of transforming growth factor alpha (TGFα) was directly related to the modulation of differentiation of monocytes into M2-like macrophages and, thereby, tumor transformation [ 21 ]. Hyaluronic acid (HA), a common component found in various tumor-associated extracellular matrices (ECM) [ 22 ], was found to contribute to the development of pro-tumor, immunosuppressive M2-like monocytes/macrophages.…”
Section: The Global Effects Of Tme On Monocytesmentioning
confidence: 99%